Loneliness Following Widowhood: The Role of the Military and Social Support. (3rd January 2020) - King, Brittany M; Carr, Dawn C; Taylor, Miles G
Abstract: Objectives: Increased loneliness is a common consequence of widowhood in later life. However, individuals with high levels of perceived social support from friends tend to cope more effectively following major social losses like widowhood. Military service is associated with cultivation of strong social support structures. This effect may not only influence those who serve, but also their spouses. Roughly half of older women today are married to veterans, which could shape how they cope with widowhood. We tested two hypotheses: (a) widows of veterans will be less lonely following widowhood compared to their nonveteran counterparts, and (b) this effect will be explained by perceived social support from friends. Methods: We used the Health and Retirement Study (HRS) to examine changes in loneliness following widowhood among wives of veterans and nonveterans. We used Ordinary Least Squares regression and mediation tests to address our hypotheses. Results: Net of baseline differences, widows of veterans reported statistically lower levels of loneliness ( p < .05) following widowhood compared to widows of nonveterans. Widows of veterans retained the same level of perceived social support from friends pre- and postwidowhood, whereas nonveteran wives experienced a loss. Perceived social support from friends mediated the association between veteran status of the deceased spouse and loneliness. Discussion: Our findings suggest wives of veterans may have more resilient social support structures than nonveteran spouses, helping them cope at widowhood. Future research should explore whether these effects persist in association with other major stressful events in later life.